2016
DOI: 10.1177/0333102416667023
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and headache: A “new” old treatment, with new findings

Abstract: Background Mindfulness refers to a host of procedures that have been practiced for centuries, but only recently have begun to be applied to varied pain conditions, with the most recent being headache. Methods We reviewed research that incorporated components of mindfulness for treating pain, with a more in depth focus on headache disorders. We also examined literature that has closely studied potential physiological processes in the brain that might mediate the effects of mindfulness. We report as well prelimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 64 publications
(63 reference statements)
0
40
0
Order By: Relevance
“…7-10 However, not every person with migraine responds to existing behavioral treatments; further, access to evidence-based behavioral migraine treatment remains a challenge to wide-scale dissemination. 15,16 Mindfulness is an attention regulation technique characterized by the nonjudgmental awareness of the present moment. 13 More than 50% of adults with migraine and severe headache report utilizing complementary and integrative health strategies for headache management.…”
Section: Introductionmentioning
confidence: 99%
“…7-10 However, not every person with migraine responds to existing behavioral treatments; further, access to evidence-based behavioral migraine treatment remains a challenge to wide-scale dissemination. 15,16 Mindfulness is an attention regulation technique characterized by the nonjudgmental awareness of the present moment. 13 More than 50% of adults with migraine and severe headache report utilizing complementary and integrative health strategies for headache management.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the "newer" generation of behavioral treatments have not yet been subjected to multiple trials, such as the Acceptance and Commitment Therapy, 16,17,42 but given initial promising findings further investigations are both warranted and needed. Incorporating standardized patient-reported outcomes, in addition to traditional headache research endpoints (ie, headache frequency and intensity, and medication intake), will help us better evaluate the effects of these treatments with respect to disability, QoL, and other relevant psychosocial aspects, such as symptoms of depression, self-efficacy, and coping abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Taken as a whole, YLDs due to primary headaches account for 69% of YLDs caused by all neurological disorders, and for 6.5% of all YLDs caused by noncommunicable disorders. 16,17 With the exclusion of the latter, there is a great body of research adressing behavioral treatments for headache disorders, showing that these are effective for a significant portion of patients, 35-50% approximately, with robust moderate effect sizes. [5][6][7][8][9][10] In recent years, nonpharmacological treatments emerged as valid options for headache disorders; these include nutraceuticals, dietary interventions, peripheral nerve or transcranial neurostimulation, acupuncture, physical therapy and exercise, and behavioral therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the behavioral approach under examination, a reduction of headache frequency of more than 35% has been found in several studies thus confirming that these approaches have the potential to positively impact headache frequency in a way that is similar to the results seen in medication trials. These treatments seem particularly helpful for both episodic and chronic migraine …”
Section: Monthly Migraine Days and Treatment Doses In Each Treatment mentioning
confidence: 99%
“…People with lower resilience are at risk for greater emotional difficulties such as depression and anxiety, particularly when associated with chronic pain conditions such as migraine. Also, studies on the use of mindfulness and ACT in migraine have demonstrated improvement in patients’ ability to tolerate pain, reduce the use of symptomatic medications and to modulate specific characteristics of the migraine personality (rigidity, low acceptance, and low resilience) . Recently, the calcitonin gene‐related peptide monoclonal antibodies (MAbs), innovative and specific, but costly pharmacological therapies have been introduced and have shown benefit in the management of both episodic and chronic migraine .…”
Section: Monthly Migraine Days and Treatment Doses In Each Treatment mentioning
confidence: 99%